1993
DOI: 10.1042/cs0840011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory action of parathyroid hormone on renin secretion in vitro: a study using isolated rat kidney, isolated rabbit glomeruli and superfused dispersed rat juxtaglomerular cells

Abstract: 1. We have previously reported that pharmacological concentrations (125nmol/l) of parathyroid hormone may stimulate renin release in the stable recirculating and non-filtering isolated rat kidney. 2. In the present study we have attempted to extend these initial observations by examining the concentration-related response of renin release to parathyroid hormone, using the same model of isolated kidney, and determining whether the effect of parathyroid hormone on renin release can be demonstrated by more direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
1
17
2
1
Order By: Relevance
“…In addition, the presence of speeific receptors for PTH and PTHRP on renal arterioles (Nickols et al 1990), the direct potent stimulatory effects of PTH (Helwig et al 1991;Saussine et al 1993a) and PTHRP (Saussine et al 1993b) on renin release, together with the regulation of PTHRP production in vascular smooth muscle cells by growth factors and vasoconstrictors including angiotensin II (Pirola et al 1993), strongly implicate this protein as a locally active autocrine/paracrine factor. Nevertheless, whether the vascular tree of the kidney is able to produce and secrete PTHRP and whether the renovascular properties of PTHRP are physiologically relevant is actually unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of speeific receptors for PTH and PTHRP on renal arterioles (Nickols et al 1990), the direct potent stimulatory effects of PTH (Helwig et al 1991;Saussine et al 1993a) and PTHRP (Saussine et al 1993b) on renin release, together with the regulation of PTHRP production in vascular smooth muscle cells by growth factors and vasoconstrictors including angiotensin II (Pirola et al 1993), strongly implicate this protein as a locally active autocrine/paracrine factor. Nevertheless, whether the vascular tree of the kidney is able to produce and secrete PTHRP and whether the renovascular properties of PTHRP are physiologically relevant is actually unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Small increases within the physiological range in PTH level reportedly improved the contractile performance of adult rat ventricular cardiomyocytes. 18 Hyperparathyroidism stimulates the synthesis of renin in juxtaglomerular cells 21 and aldosterone in zona glomerulosa cells 22 by increasing intracellular Ca 2+ level. In addition, activation of the adrenergic nervous system with a resultant elevation in circulating catecholamines facilitates To evaluate the heterogeneity of the prognostic value of lownormal PTH on admission, subgroup analysis was performed.…”
Section: Serum Pth Level and Mortalitymentioning
confidence: 99%
“…The renin-angiotensin system acts to homeostatically maintain blood pressure in response to reduced renal perfusion pressure (34,41), increased renal sympathetic nerve activity (43), or reduced NaCl intake (5,10,24). Previous studies have suggested that exogenous PTHrP may stimulate renin secretion in the isolated perfused kidney model (35).…”
Section: E460mentioning
confidence: 99%
“…PTH, acting on the common PTH/PTHrP receptor, has been reported to stimulate renin release directly from juxtaglomerular (JG) cells (34). Similarly, it has been reported that PTHrP can acutely stimulate renin release from the isolated perfused kidney at pharmacological concentrations, suggesting an effect of PTHrP on the endothelium or JG cells to directly stimulate renin release (35).…”
mentioning
confidence: 99%